2004
DOI: 10.1063/1.1818123
|View full text |Cite
|
Sign up to set email alerts
|

Steric asymmetry and lambda-doublet propensities in state-to-state rotationally inelastic scattering of NO(2Π1/2) with He

Abstract: Relative integrated cross sections are measured for rotationally inelastic scattering of NO(2Pi(1/2)),hexapole selected in the upper lambda-doublet level of the ground rotational state (j = 0.5), in collisions with He at a nominal energy of 514 cm(-1). Application of a static electric field E in the scattering region, directed parallel or antiparallel to the relative velocity vector v, allows the state-selected NO molecule to be oriented with either the N end or the O end towards the incoming He atom. Laser-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 45 publications
2
77
0
Order By: Relevance
“…In order to explore ⌳-state selected differential cross sections, a previously used crossed-beam apparatus 2,4,23,28 has been modified. The existing LIF detection system is replaced by newly designed ion optics for velocity-mapped ion-imaging.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to explore ⌳-state selected differential cross sections, a previously used crossed-beam apparatus 2,4,23,28 has been modified. The existing LIF detection system is replaced by newly designed ion optics for velocity-mapped ion-imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Early work on He-NO and Ar-NO collisions 1 resulted in integral inelastic cross sections and showed that these exhibit an oscillatory structure as a function of the final rotational state. Large anisotropy effects in the Ar-NO and He-NO potential were found by De Lange et al [2][3][4] In their experiments NO molecules were oriented, after which the integral state-to-state collision cross section was determined using laser induced fluorescence ͑LIF͒. Typically, LIF provides only integral cross sections, while differential cross sections are nowadays usually obtained using ion-imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Inspection of the V sum contour plot in Ref. 29 gives ͑at E = 500 cm −1 ͒ for a collision onto the N-end B = 4.40a 0 , A N = 5.65a 0 and for a collision onto the O-end A O = 5.25a 0 . To estimate the difference in anisotropy between the He-NO and D 2 -NO potentials, Eq.…”
Section: ͑6͒mentioning
confidence: 99%